Elements for Evaluating and Managing the Situational Complexity of Insecurity and Violence in Mexico - de la Cruz Lugardo, Pedro Isnardo; Maganda de los Santos, Manelic; Hernández Gutiérrez, José Armando; González Moreno, Vicente Enrique (Trabajo Social UNAM, 2017)
The social crisis and crisis in the State of Mexico are added to various complex social processes and phenomenon, which are necessary to understand, act upon and acquire commitment, by citizens, communities, social organizations and decision-makers. It is necessary to deconstruct the level of critical interrelationship and interdependence in the intimate, everyday sphere of violence with the sphere of public policies and government decisions on crime and its prevention.